1995
DOI: 10.1111/j.1553-2712.1995.tb03250.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Response to Out–of–hospital Death

Abstract: Objective: To better understand the perceptions, needs, and responses of family members after an out–of–hospital death. Methods: Over an 18–month period, phone interviews were conducted using a structured interview schedule modified from a similar study of survivors of in–hospital death. Subjects included 31 survivors of urban out–of–hospital deaths attended by paramedics from one ambulance company. Subjects were eligible if paramedics had arrived and death had been determined at the scene without transport. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…However, studies show that the family of a patient where CPR has been terminated generally accepts this decision and even in the case when the patient is transported from the scene they would have accepted termination at the scene. [34][35][36] We support the conservative strategy that when the ambulance professional is unsure as to whether CPR would be futile or not, CPR should be administered. This will then give the professional some time to prepare the significant others for the fact that CPR might turn out to be futile, while making reasonably sure that CPR will be futile in saving the patient's life.…”
Section: Background and Previous Researchmentioning
confidence: 82%
“…However, studies show that the family of a patient where CPR has been terminated generally accepts this decision and even in the case when the patient is transported from the scene they would have accepted termination at the scene. [34][35][36] We support the conservative strategy that when the ambulance professional is unsure as to whether CPR would be futile or not, CPR should be administered. This will then give the professional some time to prepare the significant others for the fact that CPR might turn out to be futile, while making reasonably sure that CPR will be futile in saving the patient's life.…”
Section: Background and Previous Researchmentioning
confidence: 82%
“…Patients' wishes are ignored, 4 family members and friends face prolonged suffering prior to their loved one's inevitable death, 5 fewer patients may opt for outpatient palliative care for fear their DNR order will be ignored, unwanted resuscitations tie up paramedic resources 6 and paramedics face added emotional stress. 7 Our a priori hypotheses were: 1) that EMT-Ds frequently encounter situations where they are required to resuscitate palliative care patients with DNR orders; 2) that a significant proportion of EMT-Ds comply with patient DNR orders and therefore disobey current regulations; 3) that more experienced EMT-Ds are more likely to comply with patient DNR orders; and 4) that the majority of EMT-Ds are comfortable honouring a patient's DNR order.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, researchers who have evaluated the response of family members and EMS personnel to on-scene pronouncement of death have shown that on-scene pronouncement, at least in adults, is generally well-accepted. [4][5][6] However, education of the EMS providers is central in terms of appropriate sequential procedures, including the best stepwise approaches to initiate the discussion of pronouncement of death with family members.…”
Section: Implementation Of Guidelines and Associated Concernsmentioning
confidence: 99%
“…However, resuscitation decisions in the out-of-hospital setting, including on-scene pronouncement of death, often are complicated by medical, legal, ethical, and sociological considerations for the emergency medical services (EMS) practitioner. [1][2][3][4][5][6][7] For example, according to the philosophy presented in the Uniform Determination of Death Act, 1-3 which has been adopted by many states and endorsed by both the American Bar Association and the American Medical Association, "an individual who has sustained either 1) irreversible cessation of circulatory and respiratory functions or 2) irreversible cessation of all functions of the entire brain, including brain stem, is dead. A determination of death must be made in accordance with accepted medical standards.…”
mentioning
confidence: 99%